Thermodynamic, Nonlinear Kinetic, and Isotherm Studies of Bisphenol A Uptake onto Chemically Activated Carbons Derived from Safou (Dacryodes edulis) Seeds - Cyrille Donlifack Atemkeng; Arnaud Kamdem Tamo; Giscard Doungmo; Liouna Adoum Amola; Julio Jimmy Kouanang Ngouoko; Théophile Kamgaing (Journal of Chemistry)
The interest of this work is to evaluate the possibility of using safou seeds to develop a new low-cost adsorbent and study its application to remove bisphenol A from an aqueous solution for a sustainable and ecological use of this biomass. This was done by optimizing some parameters that influence the adsorption process. The central composite design with four centre points was used to optimize the process variables. The concentration of bisphenol A solution, adsorbent dosage, stirring time, and solution pH on the adsorption capacity were considered, while the response measured was the quantity adsorbed. The activated carbon obtained by treatment with H2SO4 was named NSST and that obtained by treatment with H3PO4 was named NSPT. XRD revealed an amorphous character for the ACs, and EDXS showed they are mainly carbonaceous. Under the optimal adsorption conditions, NSPT showed the best performance. Correlation coefficients R2 and R2adj were of 85.13 and 69.12% for NSPT and 83.71 and 66.17% for NSST. A pseudo-second-order nonlinear kinetic model best described the adsorption kinetic of BPA removal by the ACs. Langmuir’s isotherm best described the adsorption of BPA onto both adsorbents. Thermodynamic studies suggested an exothermic and physisorption process.